Classification research and types of slow controlled release fertilizers (SRFs) used - a review. Issue 17 (25th September 2018) - Fu, Jiajia; Wang, Chenyi; Chen, Xianxian; Huang, Zhaowei; Chen, Daomin
ABSTRACT: Slow controlled release fertilizer (SRF) is the hot direction of new fertilizer development, but there is no unified, perfect, standardized classification basis. This paper documents a review of literature related to the classification of SRF, summarizes the history about development for the classification of SRF in three phases, proposes an improved classification of physical, chemical, and compound types. The aim of the current review is to provide evidence on which to base the selection and further development of innovative enhanced efficiency SRF. The study also further clarifies the attribution of various fertilizers and illustrates the use of representative fertilizers in each category. In addition, the compound type of SRF is given the positive perspectives.